A seasonal climatology of the upper ocean pycnocline - Sérazin, Guillaume; Tréguier, Anne Marie; de Boyer Montégut, Clément (Frontiers in Marine Science, 2023)
Climatologies of the mixed layer depth (MLD) have been provided using several definitions based on temperature/density thresholds or hybrid approaches. The upper ocean pycnocline (UOP) that sits below the mixed layer base remains poorly characterized, though this transition layer is an ubiquitous feature of the ocean surface layer. Available hydrographic profiles provide near-global coverage of the world’s ocean and are used to build a seasonal climatology of UOP properties – intensity, depth, thickness – to characterize the spatial and seasonal variations of upper ocean stratification. The largest stratification values O(10−3s−2) are found in the intertropical band, where seasonal variations of the UOP are also very small. The deepest (> 200 m) and least stratified O(10−6s−2) UOPs are found in winter along the Antarctic Circumpolar Current (ACC) and at high latitudes of the North Atlantic. The UOP thickness has a median value of 23 m with limited seasonal and spatial variations; only a few regions have UOP thicknesses exceeding 35 m. The UOP properties allow the characterization of the upper ocean restratification that generally occurs in early spring and is generally associated with large variability. Depending on the region, this restratification may happen gradually as around the Rockall plateau or abruptly as in the Kuroshio Extension. The UOP is also likely to merge intermittently with the permanent pycnocline in winter. The upper edge of the UOP is eventually close to MLD estimates, except in a few notable regions such as in the Pacific Warm Pool where barrier layers are important, and during wintertime at high latitudes of the North Pacific.